Mechanical response of a gravity cast Mg-9Al-1Zn-0.2Sc alloy at strain rates from 10-4 to 10 3 /s - Blessington, R.; Brown, A.; Lock, A.; Escobedo, J.; Hazell, P.; East, D.; Quadir, Md Zakaria (2016)
A magnesium alloy of nominal composition Mg-9Al-lZn-0.2Sc was formed into plates by die casting and underwent annealing and T4 condition heat treatments to investigate the mechanical response of varying microstructures at strain rates from 10-4-103/s in tension and compression. Full microstructural characterization was performed using optical microscopy, electron backscatter diffraction and energy dispersive x-ray spectroscopy. Quasi-static and dynamic testing was performed using a universal testing machine and a Split Hopkinson Pressure Bar in conjunction with digital image correlation for strain field mapping. Characterization and mechanical testing indicates that the T4 condition has the highest overall strength due to small equiaxed grains, a decrease in the size of ß-Mg17Al12 phase at the grain boundaries, and an increase in the size of scandium intermetallics. Testing indicates an increase in strain hardening for dynamic compression and strain rate dependence in tension; failing suddenly due to casting defects dominating the fracture mechanics. Copyright © 2016 by The Minerals, Metals & Materials Society. All rights reserved.